Interinstitutional and interstate teleneuropathology - Clayton A Wiley; Geoff Murdoch; Anil Parwani; Terry Cudahy; David Wilson; Troy Payner; Kim Springer; Terrence Lewis (Elsevier, 2011)
Background: Telemedicine has emerged as an efficient means of distributing professional medical expertise over a broad geographic area with few limitations to the various services that can be provided around the globe. Telepathology is particularly well suited to distributing subspecialty expertise in certain environments in an economical fashion, while preserving centers of excellence. Materials and Methods: After a decade of intrainstitutional teleneuropathology for intraoperative consultation, we expanded our practice to cross state lines and communicate between geographically and financially separate medical centers. Results: The result was an effective means of distributing neuropathological expertise while at the same time preserving a professional center of excellence. While technical and legal (i.e., physician licensing) barriers were surmounted, expected and unexpected issues related to communication required commitment on the part of multiple individuals with diverse expertise and responsibilities. Conclusion: Lessons learned from this successful venture can be used to facilitate future efforts in this ever-growing practical vehicle for distributing pathology subspecialty expertise.